PENERAPAN STRATEGI CONTEXTUAL TEACHING AND LEARNING (CTL)UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VSD NEGERI 010 SILIKUAN HULU KECAMATAN UKUI - Makarti, Siwi Enggar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low learning outcomes IPS. It is characterized by the acquisition of the average value of social studies students at 59.10 with the percentage of students learning completeness amounted to 50.00% from 20 students. This research is a classroom action research (PTK) which aims to improve student learning outcomes through the implementation of strategies IPS Contextual Teaching and Learning (CTL). This study was conducted in 010 primary schools Silikuan Ukui Hulu subdistrict, with research subjects fifth grade students with a number of 20 students. This study was conducted by two cycles. The data used in this study are the activities of teachers, student activities, and learning outcomes are collected using the observation technique teacher and student activities and written tests, while the analytical techniques used in this research is descriptive analysis. The study states that the acquisition of the activities of teachers and students and learning outcomes in each cycle has increased. This is supported by: (1) the percentage of activity the teachers in the first cycle of the first meeting by 45%, in the first cycle of meetings II percentage teacher activity by 52%, the percentage of teacher activity in the second cycle of the first meeting by 65%, the percentage of teacher activity in the second cycle meeting II by 75%; (2) the percentage of student activity in the first cycle of the first meeting by 49%, in the first cycle of meetings II percentage of student activity by 60%, the percentage of the activity of students in the second cycle the first meeting by 63%, the percentage of student activity on the second cycle of meeting II by 79% ; (3) learning outcomes in basic score of 59,10.Dan which reached KKM 65 only 10 students or (50%). The first cycle of the average value obtained by the students reached 63.6. Students who achieve KKM there are 13 students or 65 (65%). Cycle II average value obtained students achieve value above 67 means the KKM. Students who reached the last 16 students or (80%).